A Study of the Safety and Efficacy of Alternate Day vs. Daily Rosuvastatin Dosing in Hypercholesterolemia Patients at Tertiary Care Hospital - Yadav, Rajesh; Chhetri, Gaurav (Journal of Nobel Medical College, 2021)
Background: Many of the patients with coronary heart disease require lifelong statin administration. Patients usually discontinue the medicine either due to side effects like myalgia, hepatotoxicity or due to the cost of the medicine. The aim of this study is to see the scope of adjustment of the regimen to alternate-day dosing as an option to be considered in patients for whom adverse effects or cost are issues. Materials and Methods: A comparative, prospective, parallel group and open study was performed on forty- two patients of both genders with dyslipidaemia within the age group of 30 to 60 years attending the out – patients department of Medicine of Nobel Medical College and Teaching Hospital from February 2020 to March 2020. Mean reductions in different lipid fractions in the two treatment groups over the eight-week study period was calculated and then compared. Frequencies of patients developing different side effects was also calculated and compared between the two groups. Results: Baseline characters of both the groups were well balanced. Low density lipoprorein-C was reduced by 33.8 % in once-daily group and 31.3 % in alternate-day group, respectively. Changes were also recorded for the other lipid parameters. Such changes were found to be of no significant difference when compared between the two groups (p>0.05). Conclusion: An alternate-day regimen of statin in patients of hyperlipidaemia showed similar effect on the lipid panel compared to daily regimen.